Phylogenetic Analysis with the iPlant Discovery Environment. Issue 1 (1st June 2013) - Matasci, Naim; McKay, Sheldon
Abstract: The iPlant Collaborative's Discovery Environment is a unified Web portal to many bioinformatics applications and analytical workflows, including various methods of phylogenetic analysis. This unit describes example protocols for phylogenetic analyses, starting at sequence retrieval from the GenBank sequence database, through to multiple sequence alignment inference and visualization of phylogenetic trees. Methods for extracting smaller sub‐trees from very large phylogenies, and the comparative method of continuous ancestral character state reconstruction based on observed morphology of extant species related to their phylogenetic relationships, are also presented. Curr. Protoc. Bioinform . 42:6.13.1‐6.13.13. © 2013 by John Wiley & Sons, Inc.